Implementation practices in school improvement planning (SIP) of public city school principals - Galos, Aisha G. (College of Education, University of the Philippines Diliman, 2013)
This study aimed to investigate the implementation of public city school improvement planning (SIP) that sought to increase the achievement of urban students. In this qualitative research, the SIP implementation practices of ten public city school principals were described and their influencing factors identified. Based on interviews, survey results and the schools’ official SIP documents, analysis found that the school principals’ enumerated practices supported SIP’s objectives namely equitable access, quality and relevance, school management and school efficiency. The influencing factors identified were provisions, process, people and performance. Insufficient provisions restrained the public city school’s capacity to accept increasing student enrollment, raising student National Assessment Test (NAT) scores, maintaining positive learning environments and improving school efficiency indicators. The following are the recommendations: 1) the discovery and sharing of more innovative SIP implementation practices among school principals and 2) leveraging the identified factors to realize the school improvement plans.